Efficacy of tangential irradiation with volumetric modulated arc therapy on scalp angiosarcoma using medical linac. (November 2021) - Nakayama, Hiroki; Nakamura, Satoshi; Iijima, Kotaro; Chiba, Takahito; Takemori, Mihiro; Kashihara, Tairo; Okuma, Kae; Igaki, Hiroshi; Saitoh, Hidetoshi; Chang, Weishan; Okamoto, Hiroyuki
Highlights: Tangential irradiation was applied VMAT on scalp angiosarcoma. A structure subtracted PTV by some space from brain was selected as an avoidance structure. The brain dose was suppressed significantly by using this novel method It was suggested that the novel technique have potential to give more benefit for larger PTV. Abstract: Purpose: To increase the superficial dose and reduce the brain dose for radiotherapy of scalp angiosarcoma, we propose a novel irradiation technique of tangential irradiation volumetric modulated arc therapy (TI-VMAT). Methods: TI-VMAT and the conventional VMAT treatment plans for thirteen scalp angiosarcoma patients were created with a prescribed dose of 70 Gy. Each treatment was normalized to cover 95% of the planning target volume (PTV) with its prescribed dose. To realize TI-VMAT, an avoidance structure (AS) function was applied. AS was defined as a contour subtracted PTV by a certain space from the brain contour. TI-VMAT treatment plans for six different spaces between PTV and AS were developed and compared with the conventional VMAT treatment plan with respect to the following dosimetric parameters: homogeneity index (HI) and conformity index (CI) of the PTV, mean brain dose, and brain volume irradiated with 20% (V20% [cc]), 40% (V40% [cc]), 60% (V60% [cc]), 80% (V80% [cc]), and 100% (V100% [cc]) of the prescribed dose. Results: HI and CI were comparable between TI-VMAT and the conventional VMAT, the mean brain dose for TI-VMAT with AS defined by a space of 2.0 cm and jaw tracking was 14.27 Gy, which was significantly lower than that for the conventional VMAT (21.20 Gy). In addition, dosimetric parameters such as V20% [cc] were significantly suppressed compared to those for high doses. Conclusion: Our proposed irradiation technique TI-VMAT shows the potential to reduce radiation doses in the brain with maintaining higher dose coverage on the PTV.